THE ROLE OF DRAMA FOR GAINING LITERATURE KNOWLEDGE IN ENGLISH COURSE - Tarbiyah, Shofwatut; Putri, Nizma Amelia; Rohmana, Wahyu Indah Mala (University of Darussalam Gontor, 2024)
This article analyzes how drama can affect learning English and make it more interesting to learn.It is useful to ensure that drama as a medium to improve literary knowledge is well implemented.Drama can be used as an application of lessons in the classroom. This study was conducted at theGlobal English Course in East Java. The research methods used in this article are qualitative methodsthrough observation and interviews. An interview with one tutor was carried out as the foundationfor the analysis. The intention of studying drama is to discover how it is used for gaining literatureknowledge. The research results of the study found that drama can improve students’ pronunciation,and speaking skills and enhance confidence. Furthermore, drama can be used as the learningimplementation that has been studied throughout the course